Factors affecting the decision to choose a university of high school students: A study in An Giang Province, Vietnam - Nguyen Chi Hai; Nguyen Ho Thanh; To Minh Chau; Ta Van Sang; Vo Hoang Dong (Institute of Advanced Engineering and Science, 2023)
It is important to provide high school students with the necessary information for them to consult and make a decision to choose a university. The study aims to identify and evaluate the influence of factors in the decision to choose a university for high school students. The questionnaire survey method was used to collect data from 393 students from eight high schools in An Giang Province, Vietnam. Exploratory factor analysis and linear regression were used to analyze the data. The research results show that students are quite satisfied and quite certain with their decision to choose a university, while there are six important factors affecting the decision to choose a university. Influential factors with decreasing order of magnitude are: i) Factors consulted by teachers, family, friends, and relatives; ii) Factors of future job opportunities; iii) Factors of media activities; iv) Factors of learning conditions; v) Factors of university reputation; vi) Factors belong to the students themselves. The findings of the study show that there is no statistically significant difference between the group of males and females, between grades 10, 11, and 12. Besides, there is a statistically significant difference between students in high schools. The findings of this study have theoretical and practical implications for university admissions in Vietnam. Proposals made to university administrators were discussed. From the research results, we want to help students find the right university, and support universities to improve the efficiency of admissions.